Is Ambulatory Status a Prognostic Factor of Survival in Patients with Spinal Metastases? An Exploratory Meta‐analysis - Yang, Xiong‐gang; Han, Yue; Wang, Feng; Liu, Yong‐heng; Hu, Yong‐cheng; Lun, Deng‐xing; Feng, Jiang‐tao; Hua, Kun‐chi; Yang, Li; Zhang, Hao; Xu, Ming‐you; Zhang, Hao‐ran (Orthopaedic surgery, 2018)
This study was conducted to identify the influence of ambulatory status prior to treatment on survival of patients with spinal metastases. Two investigators independently retrieved relevant electronic literature in PubMed, Embase, and Cochrane Library databases, to identify eligible studies. Effect estimates for hazard risk (HR) were extracted and synthesized through fixed‐effects or random‐effects models as appropriate. A total of 17 eligible studies were identified, with an accumulated number of 3962 participants. HR from 14 studies regarding comparison between ambulatory versus non‐ambulatory groups were pooled using a random‐effects model, and statistical significance was presented for the pooled HR (HR = 1.96; 95% confidence interval [CI], 1.65–2.34). In subgroups of mixed primary tumor and lung cancer, ambulatory status was considered to be a significant prognostic factor (P < 0.05), while in the subgroup of prostate cancer it was not (HR = 1.72; 95% CI, 0.79–3.74). HR from 4 studies related to comparison between Frankel E versus Frankel C–D were pooled using a fixed‐effects model, which revealed statistical significance (HR = 1.73; 95% CI, 1.27–2.36). Ambulatory status is a significant prognostic factor in patients with spinal metastases. However, in patients with primary prostate cancer, the prognostic effect of ambulatory status has not yet been confirmed to be significant.